PEMBINAAN PENYUSUNAN MODUL AJAR KURIKULUM MERDEKA BELAJAR PADA GURU SEKOLAH MENENGAH PERTAMA (SMP) - Emas Marlina (JOURNAL OF COMMUNITY DEDICATION, 2022)
The problem faced by junior high school teachers is the lack of guidance in preparing lesson plans using the latest curriculum, namely the independent learning curriculum. Currently, the preparation of lesson plans in the independent learning curriculum is replaced by the term teaching module. The aim of this coaching is to facilitate junior high school teachers in compiling teaching modules for the independent learning curriculum by taking the subject, namely teachers at SMP STMC 4245 Baleendah. The method used in this activity is the identification and dissemination of the independent learning curriculum, discussion and practice of making teaching modules as well as evaluation and reflection. The result of the implementation of this community service is to provide skills in compiling teaching modules for the independent learning curriculum for SMP STMC 4245 Baleendah teachers.